The Magnitude of the 39.8 ka Campanian Ignimbrite Eruption, Italy: Method, Uncertainties and Errors - Silleni, Aurora; Giordano, Guido; Isaia, Roberto; Ort, Michael H. (Frontiers in Earth Science, 2020)
The calculation of the magnitude of an eruption needs the accurate estimate of its deposit volume. This is particularly critical for ignimbrites as no methods for their volume calculations and associated errors and uncertainties are consolidated in the literature, although invariably the largest magnitude eruptions on Earth are made of ignimbrites. The 39.8 ka Campanian Ignimbrite (CI) eruption is the largest of the Campi Flegrei caldera (Italy). The global cooling following the CI eruption and its widespread tephra affected the paleoenvironment and the migration of hominids in Europe at that time. Despite the large number of studies, the estimates of the Dense Rock Equivalent volume of the CI range between 60 and 300 km3, because of the lack of clear and reproducible methods for its calculation. Here we present a new calculation of the volume of the CI, grounded on a clear and reproducible method that can be applied universally and which provides an accurate estimation of the volume of the deposits on ground and their uncertainties and errors, allowing a strong base for further estimates of the amount of deposits eroded, covered, elutriated, which are essential for the final computation of the eruption magnitude. In order to calculate the CI volume, we reconstructed the first total isopach map of the pyroclastic density current deposit preserved on land, developed through a method that reconstructs the paleo-topography during the eruption, which is reproducible for all topographically controlled ignimbrites and allows the calculation of well-defined uncertainties in the on-land ignimbrite deposits. The preserved total extra-caldera bulk volume of the ignimbrite is estimated at 68.2 ± 6.6 km3. The total pyroclastic density current deposit volume is then corrected for erosion, ash elutriation, the intracaldera deposit volume, and the volume of tephra deposited in the sea, whereas volumes of the basal fallout deposits are taken from other studies. The total Dense Rock Equivalent volume of the eruption is 181–265 km3, whose range accounts for errors and uncertainties. This value corresponds to a mass of 4.7–6.9 × 1014 kg, a magnitude (M) of 7.7–7.8 and a volcanic Explosivity Index (VEI) of 7.